Changes in Architectural Design Concepts as A Form Adaptation After The Pandemic of Covid-19 - Ulinata (International Journal of Architecture and Urbanism, 2026)
DKI Jakarta Province is the capital city of the Republic of Indonesia which is the largest city and is developing every year. Population growth and the increasing need for buildings, urban facilities and utilities are some of the impacts of developments that occur in the capital city. The future of DKI Jakarta Province will no longer be the capital city but will become an economic center, a trade center, a business city, a financial city or a trade services city, a global or international service city. In addition, DKI Jakarta Province also has the opportunity to become a center for health, education, and culture. Environmental conditions and dense circulation are unavoidable, due to the proliferation of both commercial and residential developments in DKI Jakarta Province. From this trend, there needs to be an idea for a more effective and sustainable development concept, especially during the pandemic of Covid-19, which avoids activities in crowded areas so as to avoid crowds. COVID-19 is a pandemic that affects all sectors of the field, as a result, it is necessary to adapt designs both in terms of interior, exterior and even the built environment to adjust to the new normal order such as social distancing. Therefore, Changes in Architectural Design Concepts as A Form Adaptation After The Pandemic of Covid-19 becomes a study of how changes in architectural design concepts as a form of adaptation from the Pandemic of Covid-19 can be learned from the past for an unpredictable future because there is no who never knows when the Pandemic of Covid-19 will end or whether there will be other diseases and viruses in the future. The focus is on minimizing land use, improving the environment, and knowing changes in building design, especially buildings along with new normal conditions during the Pandemic of Covid-19 in DKI Jakarta Province. The method used is a literature study method by searching for the latest scientific books and articles, citations in scientific sources, published bibliographies and others then analyzed so that the objectives and results of the research are expected. It can be concluded that Changes in Architectural Design Concepts as A Form Adaptation After The Pandemic of Covid-19 can be a reference for the design of DKI Jakarta in the future so that DKI Jakarta becomes a friendly city that is ready to face the new normal era after the COVID-19 pandemic has passed.